Simulation model of changing working capacity of grinding equipment - Seyran Shamirovich Balasanyan; Hermine Mikhaylovna Gevorgyan (Известия Томского политехнического университета: Инжиниринг георесурсов, 2017)
The relevance of the discussed issue is caused by the necessity to develop the simulation model of equipment working capacity change in ore grinding technological systems (OGTS), which is the part of a computer model, for evaluation and analysis of its functioning efficiency considering the influence of equipment reliability indicators. The main aim of the study is to develop a simulation model of the ore grinding equipment working capacity change, formalized in the form of a random process of failures and recoveries, based on statistical data on failures and recoveries of grinding equipment of Zangezur copper molybdenum center («ZCMC» JSC, Armenia). The methods used in the study: theory of reliability, applied statistics, method of simulation modeling. The results. The authors have proposed the procedure of formalization, which allows formally introducing the change in working capacity of ore grinding equipment in the form of a random process of failures and recoveries. The composition of OGTS ZCMC was determined and the laws of working time distribution between neighboring failures and recovery time of grinding equipment were identified on the basis of statistical data on failures and recoveries of grinding equipment. Using the principle of special states the author developed the simulation model of the change in working capacity of ore grinding equipment. This model reproduces on the computer a random process of failures and recoveries of the failed equipment of OGTS in accordance with the identified distribution laws of the working time between neighboring failures and recovery time of the failed grinding equipment. Owing to the application of the modular principle and the register-based modeling method the developed modeling algorithm has compactness and certain versatility. This provides the ability to use the developed simulation model as part of computer models for evaluation and study the functioning efficiency of similar ore grinding systems. The authors estimated the adequacy of the model using the validation and verification methods with respect to the source statistical data, individual components, and simulation model in the whole. The developed simulation model was used in the computer model for evaluation and analysis of functioning efficiency of OGTS ZCMC and in the model for stochastic control of ore flotation considering the influence of indicators of equipment reliability.